Arterial tortuosity: an imaging biomarker of childhood stroke pathogenesis?. (3rd June 2015) - Wei, F; Diedrich, K; Fullerton, H; DeVeber, G; Wintermark, M; Hodge, J; Kirton, A
Abstract : Background: Arteriopathy causes most childhood arterial ischemic stroke (AIS). Mechanisms are poorly understood but may include abnormalities of arterial structure. Extracranial dissection is common while intracranial dissection may explain idiopathic focal cerebral arteriopathy (FCA). We aimed to quantify cerebral arterial tortuosity and hypothesized increased tortuosity in extracranial dissection. Methods: Children with AIS were recruited within the Vascular-Effects-of-Infection-in-Pediatric-Stroke (VIPS) study (controls from the Calgary Pediatric Stroke Program). A validated software method calculated mean tortuosity of major cerebral arteries using 3D time-of-flight MR angiography (MRA). Blinded, multi-investigator reviews defined diagnostic categories. Tortuosity was compared between dissection (spontaneous and traumatic), FCA, moyamoya, meningitis, and cardioembolic, and controls (ANOVA, post-hoc Tukey). Results: A total of 116 children were studied. Age and gender were comparable across groups. Tortuosity scores and variances were consistent with validation studies. Tortuosity in controls (1.333±0.039, n=15) was comparable to moyamoya (1.324±0.038, p=0.99, n=15), meningitis (1.348±0.052, p=0.98, n=12) and cardioembolic (1.379±0.056, p=0.19, n=27) cases. Tortuosity was higher in dissection (1.398±0.072, p=0.02, n=22) and FCA (1.421±0.076, p=0.001, n=25). Traumatic (1.391±0.036, n=9) and non-traumatic (1.403±0.090, p=0.671, n=13) scores were not different. Conclusion: Children with dissection have more tortuous arteries. Quantified tortuosity may represent a clinically relevant biomarker of vascular biology in pediatric stroke.